Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1016/s0022-5347(01)64793-1
|View full text |Cite
|
Sign up to set email alerts
|

Ureteroscopic Treatment and Surveillance of Upper Urinary Tract Transitional Cell Carcinoma

Abstract: Endoscopic treatment of upper urinary tract transitional cell carcinoma is a reasonable method to treat carefully select patients based on strict indications. Complete endoscopic followup at regular intervals is essential to rule out recurrences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(147 citation statements)
references
References 20 publications
6
137
1
2
Order By: Relevance
“…Data on distribution of stage and grade at initial presentation indicate that most patients present with a low stage (Ta-T1) grade 2 or 3 tumour [1,[6][7][8][9]. Stage and grade are the most important prognostic factors for recurrence and survival [7][8][9][10][11], but type of treatment [7] and multifocality [8,12], have also been reported to be important, to a variable extent.…”
Section: Introductionmentioning
confidence: 99%
“…Data on distribution of stage and grade at initial presentation indicate that most patients present with a low stage (Ta-T1) grade 2 or 3 tumour [1,[6][7][8][9]. Stage and grade are the most important prognostic factors for recurrence and survival [7][8][9][10][11], but type of treatment [7] and multifocality [8,12], have also been reported to be important, to a variable extent.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they are difficult to diagnose and often nondiagnostic, leading to uncertainty about treatment. The techniques for biopsy as well as specimen handling and processing are crucial and have been described previously [3,4,5]. …”
Section: Discussionmentioning
confidence: 99%
“…9 The holmium laser can also be used to safely ablate upper urinary tract tumors in patients who are not candidates for nephroureterectomy. 10 Moreover, Kuo et al reported that the use of the holmium laser with ureteroscopic access provides a safe and acceptable combination for treating the upper urinary tract in patients with bleeding diatheses. 11 The holmium laser, which is compatible with a small caliber ureteroscope, allows endoscopic ureteral incision to be done easily and precisely.…”
Section: Discussionmentioning
confidence: 99%